Neuronal Nitric Oxide Synthase Is Crucial for Ganglion Cell Death in Rat Retinal Explant Cultures - Hiroshi Katsuki; Rie Yamamoto; Daisuke Nakata; Toshiaki Kume; Akinori Akaike (Elsevier, 2004)
We examined possible involvement of nitric oxide synthase (NOS) on ganglion cell death in explant cultures of neonatal rat retina. Survival of retinal ganglion cells was significantly prolonged by a broad-spectrum NOS inhibitor Nω-nitro-L-arginine methylester. NADPH diaphorase staining revealed a diffused distribution of NOS activity in neuropils of the inner plexiform layer as well as several neurons in the inner nuclear layer. Moreover, 7-nitroindazole but not aminoguanidine promoted the survival of retinal ganglion cells. These results suggest a crucial role of neuronal NOS-derived nitric oxide in retinal ganglion cell death. Keywords:: nitric oxide, organotypic culture, retina